2017
DOI: 10.1021/acs.jpcc.7b07298
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible Light Photocatalytic Hydrogenation of CO2 into Methane over a Pd/Ce-TiO2 Nanocomposition

Abstract: A series of Ce-doped TiO 2 nanoparticles were prepared by a sol−gel process and characterized by XRD, SEM, TEM, EDX mapping, UV−vis DRS, Raman spectroscopy, N 2 adsorption−desorption, PL spectra, CO 2 -TPD, and XPS. It is found that Ce ions can enter the lattice matrix of TiO 2 and occupy of Ti sites. This atom replacement leads to the formation of impurity energy levels in the band gap of TiO 2 , extending light absorption into the visible light region. Because Ce has a more flexible valence state, both Ce 3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 59 publications
(98 reference statements)
1
13
0
Order By: Relevance
“…Li et al synthesized Pd-loaded Ce-doped TiO 2 NPs for the photocatalytic CO 2 hydrogenation of methane. [401] They observed that Ce ions can enter the matrix of TiO 2 and replace the lattice sites of Ti. This atom replacement results in the generation of impurity energy levels in the TiO 2 band gap, which in turn extends the light absorption into the VIS-light region.…”
Section: Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al synthesized Pd-loaded Ce-doped TiO 2 NPs for the photocatalytic CO 2 hydrogenation of methane. [401] They observed that Ce ions can enter the matrix of TiO 2 and replace the lattice sites of Ti. This atom replacement results in the generation of impurity energy levels in the TiO 2 band gap, which in turn extends the light absorption into the VIS-light region.…”
Section: Reductionsmentioning
confidence: 99%
“…(2017) [401] Ag-TiO 2 Suzuki-coupling of bromoaryl 20 W LED (λ > 420 nm) Toluene, 24 h, room temperature 95% conversion, 92% selectivity (2020) [413] Pd-TiO 2 Suzuki cross coupling reactions VIS light (15 W LED lamps) NaOC(CH 3 ) 3 , air atmosphere, 28 °C, H 2 O-PEG (1:1) 93% conversion, 98% selectivity (2020) [403] HUY@S-TOH@AuPd C-C coupling reactions VIS light K 2 CO 3 , ethanol-water (2:1) mixture, room temperature >99% yield (2019) [404] Pd-TiO 2 Suzuki-Miyaura cross-coupling and Ullmann homocoupling reactions VIS light (40 W CFL bulb) Base, 70 °C, 6 h 95% conversion (2016) [405] Au/Pd-TiO (2017) [406] Pd-TiO 2 /CNFs Suzuki coupling reactions VIS light (Xe lamp) Water-ethanol mixture, 50 °C, 5 h 93.6% conversion, 94.8% conversion (2017) [407] Core-Shell Ag@TiO 2 Ullmann coupling reactions Blue laser (220 mW) H 2 O/DMF/DMSO, 5 h 65% conversion (2019) [408] www.advancedsciencenews.com www.small-journal.com 2101638 (39 of 47)…”
Section: Couplingmentioning
confidence: 99%
“…The characterization results showed that Ce ions entered the TiO2 matrix at Ti sites, leading to the formation of impurity states, as shown in Figure 5. In addition, enhanced separation of the photogenerated charge carriers was also realized due to the coexistence of Ce 3+ and Ce 4+ dopant ions [34]. Anandan et al studied the photodegradation of monocrotophos under visible light irradiation with La-doped TiO2.…”
Section: Doping Of Tio2mentioning
confidence: 99%
“…The band gap energies of the photocatalysts in this study were calculated using the Kubelka-Munk formula: αhν = A(hν  Eg) η/2 , where α, h, ν, A, and Eg are the absorption coefficient, the Planck constant, the frequency of light, a constant, and the absorption band gap energy, respectively [43][44][45]. The value of η depends on the optical transition type of the semiconductor photocatalyst, and η = 1 for the systems in our study because ZnO is a direct band gap semiconductor [46].…”
Section: Structure Morphology and Ovs Of Photocatalystsmentioning
confidence: 99%